ANALYZING THE IMPACT OF REWARDS, PUNISHMENT, AND WORK ATTITUDE ON EMPLOYEE TURNOVER IN THE AUTOMOTIVE INDUSTRY - Fachrudy Asj’ari; M. Harun Arrasyid; Hartono Hartono (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2026)
Employee turnover represents an employee’s intention to leave the organization and is influenced by various organizational and behavioral factors, including rewards, punishment, and work attitude. This study aims to examine the effect of rewards, punishment, and work attitude on employee turnover at CV. Cahaya Motor. A quantitative research approach was employed using a saturated sampling technique, involving all 59 employees as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression to assess both partial and simultaneous relationships among variables. The findings reveal that rewards, punishment, and work attitude have statistically significant effects on employee turnover, both individually and collectively. These results indicate that inadequate compensation systems, ineffective disciplinary practices, and negative employee attitudes may increase turnover intention. Conversely, well-structured reward systems, fair and consistent punishment, and positive work attitudes contribute to reducing employees’ intention to leave the organization. This study highlights the importance of integrated human resource management practices in enhancing employee retention and supporting organizational sustainability.